2022
DOI: 10.1590/0100-3984.2021.0149-en
|View full text |Cite
|
Sign up to set email alerts
|

Alterations on magnetic resonance imaging of the neonatal brain: correlations with prenatal risk factors and transfontanellar ultrasound findings

Abstract: Objective: To describe the alterations seen on magnetic resonance imaging (MRI) of the brain in newborns, correlating those alterations with the transfontanellar ultrasound (TFUS) findings, and to describe the main risk factors identified. Materials and Methods: We evaluated the examinations of 51 patients who were submitted to brain MRI with a neonatal protocol during hospitalization. We evaluated the MRI findings and correlated them with previous TFUS findings, using the last TFUS performed in order to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sartori and colleagues compared the brain MRI and CUS examination results of 51 newborns (43 of them were extremely preterm infants) to verify the effectiveness of CUS in diagnosing IVH. The study showed that CUS and MRI have comparable value in identifying brain abnormalities such as germinal matrix hemorrhage, especially CUS's performance in screening and distinguishing between mild and severe hemorrhages in the germinal matrix layer (GMH) is particularly prominent [ 20 ]. Especially for preterm infants with III-IV degree cerebral hemorrhage, it can be seen that CUS is an appropriate tool for screening and follow-up of intracranial hemorrhage.…”
Section: Screening For Brain Injury In High-risk Infantsmentioning
confidence: 99%
“…Sartori and colleagues compared the brain MRI and CUS examination results of 51 newborns (43 of them were extremely preterm infants) to verify the effectiveness of CUS in diagnosing IVH. The study showed that CUS and MRI have comparable value in identifying brain abnormalities such as germinal matrix hemorrhage, especially CUS's performance in screening and distinguishing between mild and severe hemorrhages in the germinal matrix layer (GMH) is particularly prominent [ 20 ]. Especially for preterm infants with III-IV degree cerebral hemorrhage, it can be seen that CUS is an appropriate tool for screening and follow-up of intracranial hemorrhage.…”
Section: Screening For Brain Injury In High-risk Infantsmentioning
confidence: 99%